Effects of silencing neuropilin-2 on proliferation, migration, and invasion of colorectal cancer HT-29. Issue 4 (1st April 2022) - Zhan, Qi-Qi; Liu, Qian-Yu; Yang, Xin; Ge, Yu-Hui; Xu, Lei; Ding, Guan-Yi; Guo, Shang; Zhu, Bing; Xu, Wei-Guo
ABSTRACT: To investigate the effects of silencing neuropilin-2(NRP-2) on the proliferation, migration, and invasion of colorectal cancer(CRC) HT-29. Lipofectamine 2000 was used to transfect specific siRNA for NRP-2 and nonspecific control siRNA into human colorectal cancer HT-29 as the transfection group and meaningless sequence group. HT-29 cultured in a medium was used as the blank control group. The expression levels of NRP-2 mRNA in the cells were detected by real-time fluorescence quantitative PCR. The expressions of proliferation-associated protein Ki-67 in the cells were detected by immunochemical staining. Migration ability was assessed by a monolayer cell scratch wound damage and repair experiment. The Transwell chamber invasion experiment was adopted to determine invasive ability by measuring the number of tumor cells crossing the chamber membrane. Compared with the meaningless sequence group and blank control group, real-time fluorescence quantitative PCR showed that the relative expression level of NRP-2 mRNA in the transfection group was significantly decreased( P < 0.05). Results of immunochemical staining revealed that the expression of Ki-67 protein in the transfected cells was significantly reduced, and the proliferation ability was decreased( P < 0.05). The results further showed that the scratch healing rate of the transfected cells decreased after 24 h of healing( P < 0.05). Results of Transwell invasion assay showed that the number of cells passing through the stromal membrane of the upper chamber to the back of the chamber was significantly reduced in the transfection group(p < 0.05). Silencing NRP-2 could inhibit the proliferation, migration, and invasion of colorectal cancer HT-29. Graphical abstract: uf0001